Methodological strengthening in Language and Mathematics to optimizelearning in fourth grade - Leiva Torres, Jorge Ignacio; Figueroa Castro, María de los Ángeles; Arenas Angulo, Paz Alejandra; Medina Guajardo, Isabel (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
This teacher improvement project seeks to address the need to strengthen the use of active methodologies in the classroom, given the persistence of behaviorist pedagogical practices that limit student participation and innovation. Its central objective is to enhance the pedagogical skills of Language and Communication and Mathematics teachers in the 4th grade of a primary school, considering the low performance levels evidenced by formal assessments. The project methodology is based on an initial diagnostic assessment that integrates results from SIMCE and DIA tests, as well as classroom observations, allowing for the identification of pedagogical gaps and guiding methodological adjustments. Based on this assessment, the project proposes training teachers in active strategies such as Project-Based Learning and Gamification, in order to promote cognitive and social skills in students and move towards authentic assessment that responds to their real learning needs. The expected results contribute to an improvement in the quality of teaching, greater student motivation, and more active participation in the learning process. It is concluded that this proposal can be progressively applied to all educational levels, allowing for the incorporation of new active methodologies based on future assessments and the characteristics of each level.